Life Insurance Demand in Malaysia - Wong, Mei Foong (2002)
Malaysia has been identified as having the second highest saving in the world; however, less than 30 percent of Malaysia's total population of about 6.4 million is insured in 1999. The fact that a large section of the society remains uninsured means that any sudden loss of property or any personal misfortune will suffered a reduction in living standard and poverty. Besides that, savings generated by life insurance companies are crucial in providing long term savings for sustainable economic development and growth of the nation. Nevertheless, the life insurance industry in Malaysia has not been thoroughly investigated Therefore, the objectives of this study are to identify the factors contributing individual purchasing behaviour of life insurance in Malaysia, and to investigate the macroeconomic factors influence on the aggregate demand of life insurance in Malaysia. Since the demand analysis is an important component of an attempt to understand the forces driving industry growth - its past and future prospects. The empirical findings of individual purchasing behaviour of life insurance indicated significant demographic variables including the presence of children in the household, the age of the consumer, and their income level. While, the empirical finding of the multivariate Granger-causality test suggests that national income can be a stimulus to the life insurance demand in the short-run. The results of Granger-causality test also indicate that there is bidirectional causality between the price of life insurance and life insurance demand in Malaysia. Furthermore, the empirical results also showed that the interest rate significantly influence the life insurance demand in Malaysia. However, the causality tests of this study did not detect a significant short-run direct causal relationship between inflation rates and life insurance demand in Malaysia. Last but not least, the finding of the Data Envelopment Analysis (DEA) approach indicated the demand for life insurance in Malaysia is closely linked to the efficiency scores of insurance companies. Over the empirical years, most of the local constituted insurance companies operate in inefficiency state compared to the foreign Insurance companies.